Silica Physical Behavior, Geochemistry, and Materials Applications. - Heaney, Peter J. (Reviews in Mineralogy and Geochemistry Ser., 2019)
Reviews in Mineralogy & Geochemistry (RiMG) volumes contain concise advances in theoretical and/or applied mineralogy, crystallography, petrology, and geochemistry.